Dampak Aktivitas Masyarakat Terhadap Kondisi Sosial-Ekonomi Lingkungan di Bantaran Sungai Karang Mumus (Studi Kasus: RT. 32, Kampung Baru Permai Kota Samarinda) - Azzahra, Meysa Rachmadita; Adhyasta, Shafa Ayu; Utami, Alya Nindityas; Putri, Dina Hayati (Universitas Mataram, 2025)
This study aims to analyze the impact of community activities on water quality based on physico-chemical parameters and socio-economic conditions along the Karang Mumus River, RT 32 Kampung Baru Permai, Samarinda. Using quantitative (measurement of water physico-chemical parameters) and qualitative (interviews, observations) approaches, the study analyzed the impact of domestic waste and economic activities. Results showed that water quality was generally still eligible for non-consumption activities, with a temperature of 27°C, TDS of 53 ppm, salinity of 0.00%, specific gravity of 1,000, ORP of 210 mV, and pH of 8.18. The findings also show that some communities still use river water for daily needs and have limitations in waste management, despite having knowledge about the importance of maintaining environmental hygiene with the dominance of informal employment and low income (<Rp1 million/month). Economic factors and the availability of infrastructure are the main challenges in environmental conservation efforts. Estimated household economic losses due to this condition reached Rp6,331,000 per year. Strategic mitigation recommendations that are considered the most effective and possible to implement are the provision of trash bins along the riverbanks, because they are considered practical, quickly implemented, and able to encourage gradual changes in community behavior.